Modulation of host inflammatory pathways by Pseudomonas aeruginosa extracellular vesicles in cystic fibrosis: impact of pulmonary exacerbation and elexacaftor-tezacaftor-ivacaftor treatment - Said, Marianna; Burrell, Aszia; Harmon, Brennan; Krohmaly, Kylie I.; Mazur, Marina; Solomon, George M.; Hahn, Andrea (Frontiers in Immunology, 2026)
BackgroundPseudomonas aeruginosa is a prevalent pathogen in persons with cystic fibrosis (pwCF), frequently causing chronic infections. These infections are often associated with episodic pulmonary exacerbations (PEx), yet the mechanisms linking changes in P. aeruginosa to these PEx remain poorly understood. It is unknown whether virulence changes in P. aeruginosa extracellular vesicles (EVs) contribute to PEx. We hypothesized that P. aeruginosa EVs from PEx will elicit increased inflammation response compared to Pa EVs from clinical stability in an in vitro cell culture model.MethodsP. aeruginosa EVs were isolated from the sputum of pwCF collected at PEx and the immediately preceding clinical stability period. P. aeruginosa EVs or MEM control were applied apically to primary human bronchial epithelial (HBE) cells at air-liquid interface in the presence or absence of elexacaftor/tezacaftor/ivacaftor (ETI). Basal media and apical cell secretions were measured for 10 inflammatory cytokines using MesoScale Discovery (MSD) assays. RNAseq was performed on the HBE cells, with differential canonical pathways identified using Ingenuity Pathway Analysis (IPA).ResultsP. aeruginosa EVs at PEx induced reduced cytokine production in both HBE donors in the presence of ETI (p<0.001 except apical TNF-α p=0.022). The IPA results, which were hypothesis generating, suggested that the S-100 family pathway may be another measure of inflammation that is useful to study in CF.ConclusionsP. aeruginosa EVs induced HBE cell inflammation, which was reduced in the presence of ETI.